Using synovial fluid biomarkers to define a phenotype of osteoarthritis in the hip - Broomfield, JAJ (2020)
Osteoarthritis (OA) is a chronic, multi-factorial, progressive joint disease. The understanding of OA has evolved away from a wear and tear phenomenon to a complex disease of the joint taken as a whole. A method of stratifying disease, and monitoring progression, is necessary for clinical decision making and for use as end points in future research studies to develop disease modifying OA drugs (DMOADs). The creation of such a tool requires detailed understanding of the disease biopathogenesis. Synovial fluid (SF) is the most likely target to generate the insight required due to its proximity to the intra-articular structures, whose changes are fundamental to the symptomatology of the disease. No work to date has identified any useful single biomarkers of OA and for progress to be made, a consideration of a number of proteins as a panel of markers, whose interrelations describe a signature of different disease states, is required. The emergence of the slow off-rate modified aptamer scan (SOMAscan), a broad spectrum proteomic platform, presents the opportunity to analyse 1310 proteins on a single sample of fluid that measures less than 1 ml. This thesis aims to examine the utility of the SOMAscan in OA biomarker discovery by validation against traditional bench assays, use multivariate statistical analysis methods to identify candidate markers of OA disease states, and contextualise their best clinical timing in the patient pathway by examining the treatment pathways of patients from initial presentation to final treatment.